Study of the SQ3R Pop-Up Book Learning Method and Reading Ability of Elementary School Students: Studi Metode Pembelajaran SQ3R Pop-Up Book dan Kemampuan Membaca Siswa SD - Khotimah, Khusnul; Lansari, Vevy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: A lack of literacy skills often makes reading an unpopular and challenging activity, despite its importance for information retrieval and comprehension. Specific Background: To address this, selecting an engaging learning method is crucial to prevent monotony in the educational process. This study focuses on the Survey, Question, Read, Recite, and Review (SQ3R) method combined with Pop-Up Books as a potential solution. Knowledge Gap: While the SQ3R method is established, its specific application with Pop-Up Books and its effect on elementary students’ reading comprehension has not been thoroughly examined. Aims: This research aims to determine the influence of the SQ3R-based Pop-Up Book learning method on the reading comprehension skills of fourth-grade students at SD Muhammadiyah 1 Krembung. Results: Utilizing a quantitative approach with a one-group pretest-posttest design, the analysis revealed a significant finding. A paired sample t-test showed a sig (2-tailed) value of 0.000 (< 0.05), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Novelty: The integration of the SQ3R method with the interactive nature of Pop-Up Books offers a novel approach to enhance reading engagement. Implications: The findings demonstrate that the SQ3R-based Pop-Up Book method is effective in improving the reading comprehension of elementary school students. Highlights: The study found a significant improvement in students' reading comprehension. The research used the SQ3R method combined with Pop-Up Books. The method is effective in making reading more engaging for students. Keywords: SQ3R, Pop-Up Book, Reading Comprehension, Elementary Students, Educational Method